A COMMUNITY-BASED STUDY OF MILK ADULTERATION AND CHILDHOOD MALNUTRITION IN BANGALORE RURAL DISTRICT, INDIA - Mukhopadhyay, Amita; Debata, Ipsita; Kamate, Ravikiran P; Nagendra, Nagaiah; Rodrigues, Priyanka (Epidemiology and Society Health Review (ESHR), 2022)
Background: Milk promotes child growth; however, adulterated milk reduces nutritional value and exposes children to harmful chemicals. Therefore, this study aimed to assess the nutritional status of children aged 1–5 years living in the selected study area and test milk samples from the children's households for common adulterants. The study further aimed to explore the association between malnutrition and milk adulteration.Methods: We used a community-based cross-sectional study design conducted in the service area of a tertiary healthcare institute in Bangalore Rural District, Karnataka state, India. Systematic random sampling was used to recruit 180 children aged 1–5 years. Primary data was collected through interviews, anthropometry, and strip tests for milk adulteration. Statistical analysis consisted of descriptive analysis, Chi-square tests, odds ratios, and 95% confidence intervals.Results: Prevalence of underweight, stunting, wasting, and low Body Mass Index (BMI) was 13.33%, 38.33%, 15.0%, and 26.7%, respectively. General adulterants detected were neutralizers in 97 (53.9%) and maltodextrin in 90 (50%) samples. Higher proportions of stunting, underweight and low BMI were found in children drinking adulterated milk. Low BMI was significantly associated with joint family and lower maternal education.Conclusion: Our study found a high prevalence of malnutrition in children, particularly stunting. The study also detected widespread adulterants in milk and a potential association with malnutrition. The authors recommend further studies with a larger sample size to accurately delineate the relationship between milk adulteration and malnutrition.